Measuring the Stance of Monetary Policy in Vietnam: A Structural VAR Analysis - Thanh Ha, Le (Asian Journal of Economics and Empirical Research, 2015)
This study aims deriving the State Bank of Vietnam’s operating procedures based on a model that considers three channels of monetary transmission, including interest rate channel, the exchange rate channel, and the money channel. There are 4 main finding in this study. Firstly, the reactions of the money demand, exchange rate and interest rate to diverse innovations are generally consistent in different periods, but there were some changes in the period after the global financial crisis. Secondly, instead of concentrating particularly on one target, the monetary policy implementation has become more effective and pervasive, if the central bank attempts to control a combination of these targets. Thirdly, the stance measure derived from the model consistently reflects the historical performance of monetary policy which the central bank implemented to affect the GDP growth and inflation in Vietnam. Among three policy variable, the exchange rate comprises the remarkable amount of information about the policy stance. Finally, this study also examines the relationship between the stance and inflation and output growth and realizes that the theory about these relationships is statistically held in Vietnam under assumption that there is no other shock or the policy dominates other.